A low-voltage and energy-efficient full adder cell based on carbon nanotube technology - Navi, Keivan; Rad, Rabe'e Sharifi; Moaiyeri, Mohammad Hossein; Momeni, Amir (Nano-Micro Letters, 2010)
Scaling problems and limitations of conventional silicon transistors have led the designers to exploit novel nano-technologies. One of the most promising and feasible nano-technologies is CNT (Carbon Nanotube) based transistors. In this paper, a high-speed and energy-efficient CNFET (Carbon Nanotube Field Effect Transistor) based Full Adder cell is proposed for nanotechnology. This design is simulated in various supply voltages, frequencies and load capacitors using HSPICE circuit simulator. Significant improvement is achieved in terms of speed and PDP (Power-Delay-Product) in comparison with other classical and state-of-the-art CMOS and CNFET-based designs, existing in the literature. The proposed Full Adder can also drive large load capacitance and works properly in low supply voltages.